Coarsening Kinetics of a Two Phase Mixture with Highly Disparate Diffusion Mobility (Communications in Computational Physics, 2010)
The coarsening kinetics of a two-phase mixture with a large diffusional mobilitydisparity between the two phases is studied using a variable-mobility Cahn Hilliardequation. The semi-implicit spectral numerical technique was employed, anda number of interpolation functions are considered for describing the change in diffusionmobility across the interface boundary from one phase to another. The coarseningrate of domain size was measured using both structure and pair correlation functionsas well as the direct computation of particle sizes in real space for the case that thecoarsening phase consists of dispersed particles. We discovered that the average size(͞R) versus time (t) follows the ͞R10/3∝t law, in contrast to the conventional LSW theory,͞R3 ∝t, and the interface-diffusion dominated two-phase coarsening, ͞R4∝t.